2016
DOI: 10.1371/journal.pone.0164358
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in the Apoptosis-Associated Gene CASP3 and the Risk of Lung Cancer in Chinese Population

Abstract: Caspase-3 (CASP3) plays a central role in executing cell apoptosis and thus in carcinogenesis. We previously investigated the relationship between functional polymorphisms in CAPS3 829 A>C and 20541 C>T and risk of esophageal squamous cell carcinoma. However little is known about the role of CASP3 variants in susceptibility to lung cancer. To figure out the contribution of CASP3 polymorphisms to lung cancer risk, genotypes of 1000 lung cancer patients and 1000 controls were conducted by RFLP-PCR (restriction f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Nonetheless, sequence analyses of human genomes reveal extensive genetic polymorphisms in CASP3 . Some variants are associated with human cancers (39, 40), chronic periodontitis (41), and Kawasaki disease (42), raising the question of what factor may favor the maintenance of these SNPs in the human population. Here, we report that genetic polymorphisms in human CASP3 protect macrophages from S.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, sequence analyses of human genomes reveal extensive genetic polymorphisms in CASP3 . Some variants are associated with human cancers (39, 40), chronic periodontitis (41), and Kawasaki disease (42), raising the question of what factor may favor the maintenance of these SNPs in the human population. Here, we report that genetic polymorphisms in human CASP3 protect macrophages from S.…”
Section: Discussionmentioning
confidence: 99%
“…The high level of AKT1 expression was related to the drug resistance of lung cancer cells [48] . The polymorphism of CASP3 gene related to apoptosis was associated with lung cancer susceptibility, and CASP3 played a major role in cell apoptosis and carcinogenesis [49] . We found that the 1NME, a crystal structure of target CASP3 could have intense interaction with compound Acacetin.…”
Section: Discussionmentioning
confidence: 99%
“…A basic study shows that Caspase-3 (CASP3) plays an important role in promoting colon cancer cell invasion and metastasis and therefor sever as a potential target for colon cancer therapy [25]. Jia Lin et al found that CASP3 polymorphisms confer to the lung cancer susceptibility [26]. In human cancer treatment, several studies reported that patients with higher levels of procaspase-3 or active caspase-3 had a worse prognosis than patients with lower levels of procaspase-3 or active caspase-3 [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%